Awareness and Initiatives on Language Policy in Local Governments - Kandel, Basanta (Journal of NELTA Gandaki, 2021)
In Nepal, the Constitution of Nepal 2015 has abolished the centralized ruling system and established federalism which has opened up new insights into language policy issues. The Constitution empowers local government for language policy and planning, protection, promotion and use of languages, and scripts. Applying the ethnographic observation of the qualitative method, this study explores the awareness and initiatives of Nepali policymakers and language policy arbiters for the creation of language policy in local governments. Using purposive sampling, the study situates in two local governments of Gandaki Province, Nepal. The information collected through unstructured interviews, ethnographic observation, and informal interaction with language policymakers and arbiters has been analyzed and interpreted employing multiple methods. The findings show that local policy makers and actors impose multiple ideologies, therefore, language policy has become a contested issue and created a new public debate in the changing political-social and multilingual context of Nepal. Gradually, there is an increasing awareness on creating language policy, and constructive initiatives have taken for preservation and promotion of languages which is a positive way forward in the local governments by policymakers and arbiters